Comparative Study of Ocular Pharmacokinetics of Topical 0.3% Gatifloxacin Eye Gel and Solution in Rabbits - Manli Liu; Xin Zhao; Yao Yang; Qiang Yang; Jieting Zeng; Yujie Li; Xiaofeng Lin; Fang Duan (MDPI AG, 2022)
Few articles have reported drug concentrations of different ophthalmic dosage forms in the ocular tissues. This study aimed to determine the ocular pharmacokinetics of gatifloxacin 0.3% eye gel (GTX-Gel) and gatifloxacin 0.3% eye solution (GTX-Sol) at different time intervals after topical instillation in rabbits. A total of 126 healthy New Zealand rabbits were included, of which six rabbits did not receive antibiotics (control group). The remaining rabbits were randomly divided into four groups. GTX-Gel and GTX-Sol (50 μL) were topically instilled every hour in groups A1 and B1, respectively, and every two hours in groups A2 and B2, respectively, for 12 h. Ocular tissues were collected 2, 4, 8, 12, and 24 h after administration. Gatifloxacin concentration was measured using high-performance liquid chromatography coupled with tandem mass spectrometry. The drug reached peak concentrations (Cmax) in all tissues at 8-12 h. With the same administration frequency, the Cmax was higher with GTX-Gel than with GTX-Sol (p < 0.05). Except for the iris-ciliary body, other ocular tissues did not show significant difference (p > 0.05) in gatifloxacin concentration between either pair of groups. Gatifloxacin ophthalmic gel was found to attain significantly higher concentrations than the ophthalmic solution in ocular tissues.